IDENTIFIKASI ELEMEN PERMUKIMAN PULAU KABUNG DUSUN TANJUNG GUNDUL DESA KARIMUNTING KECAMATAN SUNGAI RAYA KEPULAUAN KABUPATEN BENGKAYANG - Novalina, Rantika Ayu; Kalsum, Emilya; Khaliesh, Hamdil (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
Community settlements on Kabung Island are formed by the environment, culture and characteristics of the population, the majority of whom are Bugis immigrants from outside West Kalimantan. Community settlements are located on the coast of the island and are oriented towards the sea as a place of life. This research aims to determine the characteristics of community settlement patterns by looking at the elements of settlement on Kabung Island. This research uses a survey method through observation and interviews. The composition of the settlement patterns of the Kabung Island community forms an elongated linear pattern following the coastline with settlements located on the sloping coastline and plantations located in the hills. The formation of this arrangement was caused by the activities of the community, most of whom worked at sea and was influenced by the topographic conditions of the island so that the community built on sloping plains. The spatial structure of Kabung Island is divided into highlands, lowlands or slopes, shallow seas and deep seas. The majority of people living on Kabung Island aim to earn a living, so that all areas on Kabung Island are utilized optimally to support community livelihood activities. The community culture that is still maintained today is the decorative variety that is the attraction of Kabung Island, namely the tradition of designing and moving houses.